The long noncoding RNAs PVT1 and uc002mbe.2 in sera provide a new supplementary method for hepatocellular carcinoma diagnosis. Issue 31 (August 2016) - Yu, Jinyu; Han, Junqing; Zhang, Jian; Li, Guanzhen; Liu, Hui; Cui, Xianping; Xu, Yantian; Li, Tao; Liu, Juan; Wang, Chuanxi
Abstract : Abstract: Hepatocellular carcinoma (HCC) is the most common primary malignancy of the liver in adults worldwide. Several studies have demonstrated that long noncoding RNAs (lncRNAs) are involved in the development of various types of cancer, including HCC. These findings prompted us to examine the detectability of lncRNAs in blood samples from patients with HCC. In this study, we explored the expression levels of 31 cancer-related lncRNAs in sera from 71 HCC patients and 64 healthy individuals by reverse transcription and quantitative polymerase chain reaction (RT-qPCR). We found that 25 lncRNAs could be detected in the serum and that 7 had significantly different expression levels. A 2-lncRNA signature (PVT1 and uc002mbe.2) identified by stepwise regression showed potential as a diagnostic marker for HCC. The area under the receiver operating characteristic (ROC) curve was 0.764 (95% CI: 0.684–0.833). The sensitivity and specificity values of this serum 2-lncRNA signature for distinguishing HCC patients from the healthy group were 60.56% and 90.62%, respectively. The diagnostic ability of the combination of the serum 2-lncRNA signature with alpha-fetoprotein (AFP) was much greater than that of AFP alone. The expression levels of the 2 lncRNAs were associated with clinical parameters including tumor size, Barcelona Clinic Liver Cancer (BCLC) stage, and serum bilirubin. Abstract : Supplemental Digital Content is available in the text